Single-Station Seismo-Acoustic Monitoring of Nyiragongo's Lava Lake Activity (D.R. Congo) - Barrière, Julien; d'Oreye, Nicolas; Oth, Adrien; Geirsson, Halldor; Mashagiro, Niche; Johnson, Jeffrey B.; Smets, Benoît; Samsonov, Sergey; Kervyn, François (Frontiers in Earth Science, 2018)
Since its last effusive eruption in 2002, Nyiragongo has been an open-vent volcano characterized by the world's largest persistent lava lake. This lava lake provides a unique opportunity to detect pressure change in the magmatic system by analyzing its level fluctuations. We demonstrate that this information is contained in the seismic and infrasound signals generated by the lava lake’s activity. The continuous seismo-acoustic monitoring permits quantification of lava lake dynamics, which is analyzed retrospectively to identify periods of volcanic unrest. Synchronous, high-resolution satellite SAR (Synthetic Aperture Radar) images are used to constrain lava lake level by measuring the length of the SAR shadow cast by the rim of the pit crater where the lava lake is located. Seventy-two estimations of the lava lake level were obtained with this technique between August 2016 and November 2017. These sporadic measurements allow for a better interpretation of the continuous infrasound and seismic data recorded at the closest station (~6 km from the crater). Jointly analyzed seismo-acoustic and SAR data reveal that slight changes in the spectral properties of the continuous cross-correlated low-frequency seismo-acoustic records (and not solely the single LP events) can be used to track fluctuations of the lava lake level on a daily and hourly basis. We observe that drops of the lava lake and the appearance of significant LP “lava lake” events are a consequence of deep magma intrusion, which induces changes in the shallow magmatic system. This study highlights the potential to continuously monitor Nyiragongo’s lava lake activity (and subsequent information about pressure changes within the magmatic system) using a single seismo-acoustic station located several kilometers from the vent.